Assessment of the Knowledge and Perception Regarding Breast-feeding and Immunization Among the Post-natal mothers at a Tertiary Care Hospital, Bangalore - A Cross-sectional Study - Chaithra S; Ranganath T S (RGUHS Journal of Medical Sciences)
Background Breastfeeding and immunization play a pivotal role in ensuring infant and child well-being encompassing vital aspects of survival nutrition growth and development. Maternal and child health is a critical concern globally with significant implications for public health. This study aimed to assess the knowledge and awareness of breastfeeding and immunization practices among postnatal mothers and the associated factors intertwined with these practices.Methods A descriptive cross-sectional study was conducted from August to September 2023 involving 262 post-natal mothers admitted to post-natal wards inborn wards Kangaroo-mother-care KMC and post-partum care units at Vanivilas Hospital Bangalore. Using a pre-tested semi-structured questionnaire data were collected through a face-to-face interview method were entered in Microsoft-Excel and analysed using SPSS version 26.0.Results The study showed that postnatal mothers had strong knowledge about breastfeeding and immunization with 92.4 planning to exclusively breastfeed. Most avoided pre-lacteal feeds 90.8 and started breastfeeding within 2-3 hours of delivery 42.8. A high percentage 87 were aware of colostrum benefits and most adhered to frequent feeding schedules. Mothers also showed strong commitment to following the National Immunization Schedule.Conclusion The study revealed that most postnatal mothers had good knowledge of breastfeeding and immunization with a strong commitment to exclusive breastfeeding and timely immunization. However gaps in awareness about adequate feeding signs suggest the need for enhanced prenatal education and increased support from lactation consultants to improve the feeding practices.